Indicators of fraudulent financial reporting: Malaysian evidence / Dr. Suhaily Hasnan, Prof. Dr. Rashidah Abd. Rahman and Prof. Dr. Sakthi Mahenthiran - Hasnan, Suhaily; Abd. Rahman, Rashidah; Mahenthiran, Sakthi (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
This study examines ten indicators associated with fraudulent financial reporting (FFR) in Malaysian public listed companies. We hypothesize that three indicators proxy for management rationalization, four indicators proxy for management motives, and three indicators proxy for the opportunity to commit fraud. Our sample consists of 53 fraud firms convicted of securities fraud and 53 no-fraud firms, which were listed on the Bursa Malaysia and for whom complete set of data is available from 1996-2007. With regard to rationalization, we find that prior violations and founders on the board are positively and significantly associated with FFR, and with regard to motive, we find that financial distress is positively and significantly associated with FFR while family ownership is negatively and significantly associated with FFR. Opportunity for fraud proxies multiple directorships on boards and audit quality are positively and significantly associated with FFR. Additionally, the study finds that earnings management in prior years leads to FFR. The findings of this study have important implications for public policy makers in respect of their future efforts in preventing and reducing the occurrences of FFR. The study should also provide useful insights to auditors, regulators, investors, and other financial statement users about the characteristics of fraud firms. By better understanding these characteristics, financial statement users should be in a better position to identify and curtail fraudulent activity in the future.